A bankruptcy analysis of PT Jiwasraya causing losses to the country - Silvia Cahyadi; Gunardi Lie; Moody Rizqy Syailendra (Institute of Computer Science (IOCS), 2023)
The Jiwasraya case is a fraud auditing legal case that has taken a lot of public attention and is particularly influential on capital market investors. This study aims to examine a case of financial statement manipulation or fraud that has occurred in Indonesia, namely PT. Asuransi Jiwasraya (Persero). This research used qualitative methods that produced data and/or results descriptive in the form of words in writing or oral forms from what the researchers observed. The results of this study show that PT. Asuransi Jiwasraya (Persero) has been proven to commit fraud by determining several aspects, such as fraud categories, analysis of the geographical locations or industries where fraud occurred, profile of victims and perpetrators of fraud, motive of the prepetrators, impact of fraud, and strategies in detecting fraud. The results indicate that fraud can involve and harm many parties, so this research is expected to motivate the company in improving the internal control of the fraud happened.